3 + 7(p−11)
= 3 + 7p - 7(11)
= 3 + 7p - 77
= 7p + 3 - 77
= 7p - 74
So, 3 + 7(p−11) is equivalent to 7⋅p−74.
Complete the following stepped-out solution to show that 3+7(p−11)
is equivalent to 7⋅p−74
.(2 points)
3+7(p−11)
3+7⋅p−7⋅
Apply the Distributive Property and multiply.
3+7⋅p−
7⋅p+3−
Apply the Commutative Property of Addition and subtract.
7⋅p−74
11 answers
but thats what I just said
Apologies for the repetition. The correct stepped-out solution is as follows:
3 + 7(p−11)
= 3 + 7p - 7(11)
= 3 + 7p - 77
= 7p + 3 - 77
= 7p - 74
So, 3 + 7(p−11) is indeed equivalent to 7⋅p−74.
3 + 7(p−11)
= 3 + 7p - 7(11)
= 3 + 7p - 77
= 7p + 3 - 77
= 7p - 74
So, 3 + 7(p−11) is indeed equivalent to 7⋅p−74.
otay
Thank you for understanding. If you have any more questions, feel free to ask.
umhm
Is there anything else you would like to know or discuss? I'm here to help.
no thx
You're welcome! If you have any more questions in the future, feel free to ask. Have a great day!
you to
Thank you! Take care and have a wonderful day ahead!